A comprehensive study on the impact of RGO/MWCNT hybrid filler reinforced polychloroprene rubber multifunctional nanocomposites. (July 2020) - Maya, M.G.; Abraham, Jiji; Arif P, Mohammed; Moni, Grace; George, Jinu Jacob; George, Soney C.; Thomas, Sabu
Abstract: Flexible dielectric chloroprene rubber (CR) nanocomposites reinforced by one-dimensional carbon nanotube (CNT)/two dimensional reduced graphene oxide hybrids have been prepared using two-roll mill mixing technique. Non-covalent π-π interaction between multiwalled carbon nanotubes (MWCNTs) and reduced graphene oxide (RGO) nanosheets and the secondary interaction between fillers and chloroprene rubber matrix are responsible for generating the effective load transfer between RGO/MWCNTs and CR. The prepared RGO-MWCNT hybrid nanocomposites with high dielectric constant (≈650), low dielectric loss (≈0.42) and high energy storage efficiency (78.6%) values are practically good enough to use as a low cost polymeric dielectric layer in transistors. Furthermore, the prepared nanocomposites showed excellent electromagnetic effectiveness; a maximum shielding efficiency of 11.87 dB @ 3.5 GHz was achieved at 4 phr of MWCNT loading. This excellent electromechanical performance can be ascribed to the synergistic effect of RGO-MWCNT hybrid suggesting that this novel hybrid nanocomposite serves as an attractive candidate in modern electronics and electric power systems. Graphical abstract: Image 1 Highlights: Chloroprene rubber/ RGO-MWCNT nanocomposite was prepared by two roll mill mixing method. Nanocomposite was characterised by static, dynamic mechanical and microtructural analysis. Nanocomposites exhibited high dielectric constant, low dielectric loss and high energy storage efficiency. Optimum hybrid concentration is found to be 0.9 phr (RGO) and 4 phr (MWCNT).